The Role of Psychological Well-Being in Mediating the Impact of Emotional, Spiritual, and Intellectual Intelligence on Lecturer Performance, Moderated by Job Demands - Enny Istanti; Musriha Musriha; RM Bramastyo KN; Achmad Daengs GS (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the role of psychological well-being as a mediator in the influence of emotional, spiritual, and intellectual intelligence on lecturer performance, with job demands as a moderating variable. The study used a quantitative design with a survey method on 130 university lecturers. Data were collected through a structured questionnaire that measured emotional, spiritual, intellectual intelligence, psychological well-being, job demands, and lecturer performance, then analyzed using structural equation modeling (SEM-PLS). The results showed that emotional intelligence did not significantly influence lecturer psychological well-being or performance. Intellectual and spiritual intelligence had a significant positive effect on psychological well-being, but did not have a direct impact on performance. Psychological well-being was also not proven to be a mediator in the relationship between the three intelligences and performance. Conversely, job demands had a strong and significant direct influence on lecturer performance, although its moderating role in the relationship between psychological well-being and performance was not supported. These findings confirm that external factors such as workload and job pressure are more dominant in determining lecturer performance than internal psychological factors. Practically, the implications of this study encourage universities to manage workload distribution proportionally, provide organizational support, and create a conducive work environment. Theoretically, this study enriches the Job Demands–Resources framework by demonstrating that psychological well-being has a limited impact when job demands are high. Future research is recommended using more valid instruments and longitudinal designs to gain a deeper understanding.